Unveiling The Effectiveness Of Utilizing AI As Tool for Language Learning and Teaching - Williams-Onyeji, Paulina Oluwafunmilayo (UIR Press, 2025)
Artificial Intelligence (AI) is an effective tools that enhances innovative advancement in education, especially in language learning. It further help bring to the know the promises and challenges associated with AI's impact in language education. This objective of the study unveils the numerous AI tools engaged for language learning, such as speech technology, chatbots, machine translation and AI-generated content. On the one hand, it provide benefits which vary from interactive engagement, progress tracking and personalized guidance. This research engage the combination of survey techniques from sample of 34 respondents and library methodology. This paper conclude that explorering AI technologies enhance innovative learning experience in education especially in language by catering to both institutional and individual needs, enabling flexible and self-paced learning if the recommendation of this study is adopted.